Analysis of Carrot Farming Income in Barusjahe District, Karo Regency, North Sumatera Province - Wahyuni, Ira; Fathoni, Zakky; br Ginting, Windiyanta (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This research aims to: (1) To describe the picture carrot farming in Barusjahe District, Karo Regency, (2) Foranalyze the costs, receipts and income obtained by carrot farming in Barusjahe District, Karo Regency, (3) To analyze feasibility carrot farming in Barusjahe District, Karo Regency. Research methods used is a survey method with a quantitative descriptive approach. Location determination was carried out deliberately (purposive sampling) with considering that Barusjahe District is a carrot production center largest in Karo Regency. The research sample was 60 farmers taken deliberately from three villages, namely Barusjahe Village, Sukanalu Village, and Desa Cape Barus. Data analysis was carried out by calculating total costs, revenue, income, and feasibility of farming through R/C, B/C, and point ratios break even (BEP). The research results show that the average total cost of farming carrots amounting to IDR 27,283,491/Ha/MT, average revenue of IDR66,435,973/Ha/MT, and net income of IDR 39,683,176/Ha/MT. Mark An R/C ratio of > 1 indicates that carrot farming in the District Barusjahe is worthy and profitable to cultivate. The most important factor affecting farmers' income are land area, labor costs, and prices sell the harvest.